Application of modified chitosan in tannery wastewater treatment - Romero-Sevilla, M.L.; Sánchez-Cuadra, S.M.; Benavente Silva, M. (Nexo Revista Científica, 2018)
In this study, the adsorption capacity of chromium VI in copper-modified chitosan (Chitosan-Cu) and in zinc-modified chitosan (Chitosan-Zn), and its application in tannery wastewater were compared. This work included the study of the pH of maximum adsorption capacity in a range of 3 to 6 and the adsorption equilibrium of Cr (VI) at different concentrations (from 1.0 to 750.0 mg / l) and different masses of modified bio-adsorbents (5 and 2 g). The results showed that the adsorption of chromium VI in the two modified bioadsorbents depends strongly on the pH of the solution, where the highest percentage of chromium VI removal was reached at pH 3. The evaluation of the data Experiments of the adsorption equilibrium of Cr (VI) applying the Langmuir and Freundlich models shows that in all cases there was a better fit of the data to the Freundlich model and that the maximum adsorption capacity was reached in the Chitosan-Cu adsorbent. Also, the results indicated that the Chitosan-Cu adsorbent was more effective in the removal of Cr VI from tannery wastewater with 98%.